2003
DOI: 10.1034/j.1600-0447.2003.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Asperger's disorder: a case report of repeated stealing and the collecting behaviours of an adolescent patient

Abstract: A wide variety of bizarre behaviours and so-called borderline behaviours occur in late adolescence and adult life of patients with Asperger's disorder. But classic schizophrenia is very rare. Psychiatrists unacquainted with the clinical diagnosis/context may find it difficult to evaluate 'concrete', 'childish', or 'bizarre' symptoms in patients with Asperger's disorder, and thus are prone to misdiagnose them as having schizophrenia disorders or other similar disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Clinical case studies of people within the professional literature ( Baron-Cohen 1988;Barry-Walsh and Mullen 2004;Chen et al 2003;Chesterman and Rutter 1993;Cooper et al 1993;Everall and LeCouteur 1990;Fujikawa et al 2002;Kohn et al 1998;Haskins and Silva 2006;Mawson et al 1985;Murrie et al 2002;Schartz-Watts 2005) have also explored the hypothesised relationship. Sexual offences, violent offences, and arson tend to be the most offence types described within these studies, while preoccupations and special obsessions, interpersonal naiveté, low empathy, self-centredness, 'logical' explanations for offending and problems with sexual frustration are all described as contributory characteristics to offending.…”
Section: Introductionmentioning
confidence: 96%
“…Clinical case studies of people within the professional literature ( Baron-Cohen 1988;Barry-Walsh and Mullen 2004;Chen et al 2003;Chesterman and Rutter 1993;Cooper et al 1993;Everall and LeCouteur 1990;Fujikawa et al 2002;Kohn et al 1998;Haskins and Silva 2006;Mawson et al 1985;Murrie et al 2002;Schartz-Watts 2005) have also explored the hypothesised relationship. Sexual offences, violent offences, and arson tend to be the most offence types described within these studies, while preoccupations and special obsessions, interpersonal naiveté, low empathy, self-centredness, 'logical' explanations for offending and problems with sexual frustration are all described as contributory characteristics to offending.…”
Section: Introductionmentioning
confidence: 96%
“…The possible presence of antisocial and criminal behaviour in a subsample of individuals with Asperger syndrome has been a topic of high interest in the literature recently (Allen et al 2008;Barry-Walsh and Mullen 2004;Ghaziuddin et al 1991;Haskins and Silva 2006), a number of papers have reported on single cases of offenders with AS (e.g. BaronCohen 1988;Chen et al 2003;Milton et al 2002;Schwartz-Watts 2005) or pointed to a high prevalence of AS among offenders and special hospital patients (Hare et al 1999;Scragg and Shah 1994).…”
Section: Introductionmentioning
confidence: 97%
“…Larsen and Mouridsen reported that 22% of individuals diagnosed with AS got married (15). However, it was also reported that their marriage did not last long and divorce rate was high (16). We also learned that our patient did not have a girlfriend, nor did he attempt to get into a relationship.…”
Section: Discussionmentioning
confidence: 73%
“…Especially in late adolescence, limited social relations and weird behaviors can suggest schizophrenia. However, it is very rare for schizophrenia to accompany AS (16). Schizophrenia and other psychotic disorders were excluded from the diagnosis of our patient as delusions, hallucinations, disorganized speech and behaviors during his disease period were never identified in the history received from the patient and his family.…”
Section: Discussionmentioning
confidence: 99%